Analisis Perilaku Konsumen Pembeli Thrifting dalam Perspektif Ekonomi Syariah: Studi Kasus di Pasar 3-4 Ulu Palembang - Msy. Aziza Septiani; Cholidi; Deky Anwar (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Understanding consumer behavior is very important. By understanding consumer behavior, marketers can provide and offer offers that can attract consumers' interest in purchasing Thrifting. The means used to carry out thrifting transactions are quite varied, namely they can be done online or offline. The type of research in this research is qualitative research. This research uses data collection techniques as follows: documentation, observation, interviews and literature study. The type of data used is primary data obtained from interviews with informants regarding consumer behavior of thrifting buyers from a Sharia Economics perspective, while secondary data obtained comes from books, journals and articles. The results of the analysis show that the consumer behavior of thrifting buyers is due to the good quality of the goods, the price is cheap, consumer behavior occurs due to the influence of friends, family or people around them, while the factors that influence the decision to purchase thrifting are the choice of branded products, brand, place of distribution, time of purchase. , purchase amount, and payment method